Enhancing learning through technology - Sorensen, Elsebeth Korsgaard; O Murchu, Daithi; Gale Group (Hershey, Penn. Information Science Pub., 2006)
"This book identifies and presents the latest research on theory, practice, and capturing learning designs and best-practices in education"--Provided by publisher.
Preface -- Online communities and professional teacher learning: affordances and challenges -- Enhancing phronesis: bridging communities through technology -- Enhancing the design of a successful networked course collaboration: an outsider perspective -- Enhanced learning and leading in a technology rich, 21st century global learning environment -- Enhancing learning through 3-D virtual environments -- Inquisitivism: the evolution of a constructivist approach for web-based instruction -- Situated learning and interacting with/through technologies: enhancing research and design -- Rethinking e-learning: shifting the focus to learning activities -- Computer-supported collaborative learning and the central research questions: two illustrative vignettes -- Identifying an appropriate, pedagogical, networked architecture for online learning communities -- Ms. Chips and her battle against the cyborgs: Embedding ICT in professional praxis -- Making sense of technologically enhanced learning in context: a research agenda -- Brain-based learning -- About the authors -- Index.
Electronic reproduction.
Keywords: Educational technology; Learning; Electronic books